36.5k views
0 votes
(-15)-(-3) =

(1-7)+(+5) =
(+5) x ( +6 ) =
(+18 ) + ( +6)
(9)+( 8 ) =
(+10)-(+1) =
( +4 ) x ( 3 ) =
( 12 ) + ( +4 ) =
(+6) + (6)
(+11)-(7) =
(-8) x ( +2 ) =
(+15) + ( 3 ) =
(*12 ) + ( 4) =
(8) - ( +2) =
(-7) x ( -5 ) =
(-10 ) = (-2) =

User MathBunny
by
4.7k points

1 Answer

6 votes

Answer:

(-15)-(-3) = -12

(1-7)+(+5) = -1

(+5) x ( +6 ) = 30x

(+18 ) + ( +6) 24

(9)+( 8 ) = 17

(+10)-(+1) = 9

( +4 ) x ( 3 ) = 12x

( 12 ) + ( +4 ) = 16

(+6) + (6) 12

(+11)-(7) = 4

(-8) x ( +2 ) = -16x

(+15) + ( 3 ) = 18

(*12 ) + ( 4) = 4

(8) - ( +2) = 6

(-7) x ( -5 ) = 35x

HOPE THIS HELPS : D I TOOK A LOT OF WORK ON THIS <3

User Jerome VDL
by
4.6k points